Pengaruh Bauran Pemasaran Terhadap Kepuasan Konsumen Dalam Mengembangkan Coffe Shop Di Kota Solo Raya - Rizki Darmawan Prasetya; Nur Fajar Ali Maulana; Rayhan Gunaningrat; R. Taufiq Nur Muftiyanto (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
Indonesian coffee is one of the leading agricultural products besides palm oil and rubber. Coffee production It is anticipated that Indonesia will be able to compete with the world market. The increasing trend of drinking coffee is also felt by Indonesian people, as evidenced by the increasing number of cafes offering coffee products at prices ranging from tens of thousands of rupees to hundreds of thousands of rupees. In order for the coffee business strategy to survive and survive, an integrated marketing strategy is needed that pays attention to consumer satisfaction and whether consumer satisfaction influences the development of cafes. The purpose of this study is to determine whether customer satisfaction at Solo Raya coffee shops is influenced by the marketing mix. The sampling method uses quota sampling and random sampling methods, and the criteria for respondents are consumers who have purchased coffee products in the last month, totaling 104 respondents. Surveys distributed online or electronically using Google Forms will be used for data collection. Studies indicate that consumers' purchasing decisions are significantly influenced by their location. The F test results demonstrate that each component of the marketing mix, whether used separately or in combination, significantly influences consumers' decisions to buy.